2016
DOI: 10.12944/crnfsj.4.special-issue-october.19
|View full text |Cite
|
Sign up to set email alerts
|

Super foods and Super herbs: Antioxidant and Antifungal Activity

Abstract: Antioxidant activities and phenolic contents of selected superfoods and superherbs, cultivated in regions of Greece, were investigated so as to supply new information on their antioxidant function. The total antioxidant capacity was estimated by DPPH• (1,1-diphenyl-2-picrylhydrazyl radical) assay while total phenolics were measured using Folin–Ciocalteu method. Moreover this study was carried out with a supplementary objective to investigate the antifungal activities of the selected superfoods/superherbs extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
7
0
5
Order By: Relevance
“…followed by raspberries (1.41 ± 0.11 mg AAE/g), blackberries (1.12 ± 0.07 mg AAE/g) and strawberries (1.11 ± 0.12 mg AAE/g). In the previous study, the free radical scavenging activity of blueberries were observed to be 65.07 ± 0.04 mg AAE/g [ 44 ], raspberries were 395.80 AAE/g [ 44 ], strawberries ranged between 3.33–21.08 mg AAE/g d.w. [ 45 ] and blackberries leaves with 111.5 mg AAE/g d.w. [ 46 ] which showed higher values when compared to our study. The difference in results might be due difference in varieties, growing region, extraction solvent, solute to solvent ratio, harvesting season and maturation stages of berries.…”
Section: Resultsmentioning
confidence: 99%
“…followed by raspberries (1.41 ± 0.11 mg AAE/g), blackberries (1.12 ± 0.07 mg AAE/g) and strawberries (1.11 ± 0.12 mg AAE/g). In the previous study, the free radical scavenging activity of blueberries were observed to be 65.07 ± 0.04 mg AAE/g [ 44 ], raspberries were 395.80 AAE/g [ 44 ], strawberries ranged between 3.33–21.08 mg AAE/g d.w. [ 45 ] and blackberries leaves with 111.5 mg AAE/g d.w. [ 46 ] which showed higher values when compared to our study. The difference in results might be due difference in varieties, growing region, extraction solvent, solute to solvent ratio, harvesting season and maturation stages of berries.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-aflatoxigenic efficacy of the CI plant against Aspergillus parasiticus was also studied [9]. The tested extracts of CI [10] inhibited the growth of A. parasiticus and Aspergillus carbonarius .…”
Section: Introductionmentioning
confidence: 99%
“…An increasing trend in the food, pharmaceutical, and cosmetic industry is the utilization of natural plant extracts or plant-derived compounds, as an alternative to the application of chemical or synthetic antimicrobials to combat spoilage microflora and pathogens [1,2]. Furthermore, the nontoxic nature of chemicals in plants, positive healthy properties, consumer perception and acceptance of their use has been well demonstrated [3,4].…”
Section: Introductionmentioning
confidence: 99%